Modern Transportation and Photovoltaic Energy for Urban Ecotourism - Raffaella AVERSA; Relly Victoria V. PETRESCU; Antonio APICELLA; Florian Ion T. PETRESCU (Transylvanian Review of Administrative Sciences, 2017)
This study proposes an innovative integrated transportation/photovoltaic energy system that will enable the Pompeii Municipality to develop a set of urban ecotourism policies and instruments for the preparation and adoption of an environmental sustainable mobility strategy to be applied in their future municipality urban plan. The innovative character of the study resides in two principal aspects: the technologies applied, namely, the use of thin fi lm photovoltaic (hereafter PV) panels (copper-indium-gallium-(di)selenide cells) on a fl exible support, and the way these technologies are applied. A combined energy/mobility approach based on ‘Zero km and zero emission energy production for zero emission electric transportation strategy’ to be implemented in the Public Urban Plan (Piano Urbanistico Comunale) of the town of Pompeii is presented. According to the technology to be adopted (thin PV fi lm on fl exible supports integrated in the parking shelters roofs), to the foreseen PV plant of 700 sqm parking lots, and to an innovative multifunctional design approach (bio-mimicking sun track roof), an improved yearly power production of 100.0 MWh is foreseen with a 20- 25% increase of power production with respect to standard fi xed PV panels of the same type.